Microbial forensics - Budowle, Bruce, 1953-; Schutzer, Steven E.; Morse, Stephen A. (Academic Press, 2020)
"Microbial Forensics, Third Edition serves as a complete reference on the discipline, describing the advances, challenges and opportunities that are integral in applying science to help solve future biocrimes. New chapters include: Microbial Source Tracking, Clinical Recognition, Bioinformatics, and Quality Assurance. This book is intended for a wide audience, but will be indispensable to forensic scientists and researchers interested in contributing to the growing field of microbial forensics. Biologists and microbiologists, the legal and judicial system, and the international community involved with Biological Weapons Treaties will also find this volume invaluable"--